International food security regulation - Semin, Alexander N.; Kurdymov, Alexander V. (Opción, 2019)
This article is devoted to the international food security architecture assessment. Research object includes different international agencies, created since 1942, which performance is directly or indirectly related to food security, as well as the regulatory legal acts. The research hypothesis is that the quality of international regulation positively correlates with the quality of food security. This article analyzes the international agencies in a sub-objective, retrospective and level context through the institutional methodology. Based on the research, there are assessed the main development trends occurring in the field of international food security regulation in the light of new challenges and threats.